THE ANALYSIS LANDSLIDES POTENTIAL DUE TO CHANGES OF LAND-USE IN MIU WATERSHED - Izza Nadrata Tamrin (Jurnal Sains dan Teknologi Tadulako, 2022)
This study aims to determine the magnitude of land-use change in the Miu watershed and to determine the relation between slope and soil type to erosions. The method used to predict the rate of erosion is the Universal Soil Loss Equation (USLE) in 2005, 2010, and 2016 with the help of the Geographic Information System (GIS). This study uses data on rainfall, slope, soil type, land use, and conservation and crop management factors which are then entered into the USLE equation. From this equation, the actual erosion rate in 2005 was 2,634,104.25 tons / year, 2010 was 3,285,025.34 tons / year, and 2016 was 1,856,140.79 tons / year. The average actual erosion in 2005, 2010, and 2016 was 2,591,756.79 tons/year, which is classified as minor erosion. The landslide-prone area based on the lowest slope of 5.50% is equivalent to an area of ​​36 km2, for the medium it is 34.81% equivalent to an area of ​​228 km2, and a height of 59.69% covering an area of ​​391 km2 where very steep slopes dominate this river basin. The effect of significant land-use change affects the rate of erosion when there is a high intensity of rain on a steep slope so the potential for erosions in the area.